1968
DOI: 10.1111/j.1432-1033.1968.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl‐Terminal Region of Human and Bovine Erythrocyte Carbonic Anhydrases

Abstract: 1. Carboxyl-terminal sequences have been determined for forms B and C of the human erythrocyte carbonic anhydrase and form B of the bovine enzyme. The proteins were degraded with CNBr, and peptide fragments of 20 residues were isolated from human enzyme C and bovine enzyme B while the human B form gave a fragment consisting of only 19 residues. The sequences of these fragments were determined and by carboxypeptidase digestion of the whole proteins it was shown that they represent the carboxyl-terminal part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…BCA, as supplied by Sigma, is a mixture of the isoforms BCA-A and BCA-B. The amount of the isoform A present in the mixture from bovine erythrocytes is negligible compared to the isoform B (26). The data reported in this paper were obtained using BCA (c-3934), and similar results were obtained with bovine carbonic anhydrase B (c-2522)).…”
Section: Materials-bovine Carbonic Anhydrase (Bca)supporting
confidence: 68%
“…BCA, as supplied by Sigma, is a mixture of the isoforms BCA-A and BCA-B. The amount of the isoform A present in the mixture from bovine erythrocytes is negligible compared to the isoform B (26). The data reported in this paper were obtained using BCA (c-3934), and similar results were obtained with bovine carbonic anhydrase B (c-2522)).…”
Section: Materials-bovine Carbonic Anhydrase (Bca)supporting
confidence: 68%
“…Our hypothesis was supported when the reactivity of the two conformers towards CP‐Y was studied. It has been reported that wild‐type BCAII is poorly attacked by CP‐Y [33], however, when the C‐terminal tertiary structure is perturbed (as in the denatured state), it is readily hydrolyzed from the C‐terminus [8]. We therefore analyzed the susceptibility of the two conformers to CP‐Y by mass spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The B isoenzyme derivative studied is one prepared by carboxymethylation of a histidine at position 200 in the recent amino-acid sequence (5), the same histidine previously assigned (2,4) to position 204. The C isoenzyme, which is probably homologous to the B form (4)(5)(6), has a leucine replacement at the corresponding position 198 in its sequence (4,5). However, Gothe and Nyman (7) have been able to alkylate a histidine close to position 63 in the C isoenzyme * This is paper No.…”
mentioning
confidence: 99%